The Effect of Paitan Leaf Pesticide Concentration (Tithonia diversifolia) On The Presence of Spider Predators on Edamame Plants (Glycine max (L.) Merill) - Juniawan, L. Akhmad; Sarjan, M.; Fauzi, M. Taufik (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Edamame (Glycine max (L.) Merril) is a legume commodity with high economic potential, and its production demand continues to increase in both domestic and export markets. However, edamame productivity is often constrained by pest attacks (OPT) such as Spodoptera litura, Etiella zinckenella, Riptortus linearis, and other major pests. In this study, the presence of spider predators in edamame plants was examined in relation to different concentrations of a botanical pesticide derived from paitan leaves (Tithonia diversifolia). Using a Randomized Block Design (RBD) with six treatments (P0, control), P1, P2, P3, P4, and P5, each with four replications, the study was place in Sembalun Village, East Lombok Regency, from May to July 2024. Three indices—the dominance index, the abundance index, and the Shannon-Wiener diversity index (H')—were used to evaluate the data. The results showed 6 spider genera from 5 families, with Pardosa and Pirata being the most dominant. The highest population was found in the control (P0) and decreased with increasing pesticide concentration. The highest diversity index was at P0 (H’=1.382) and the lowest at P5 (H’=1.222), with the evenness index categorized as moderate and the highest dominance index at P2 (0.372). In conclusion, higher concentrations of paitan leaf extract reduced the presence of spider predators, indicating that its application should consider appropriate doses to avoid harming natural enemies.